Translation-Targeting RiPPs and Where to Find Them - Travin, Dmitrii Y.; Bikmetov, Dmitry; Severinov, Konstantin (Frontiers in Genetics, 2020)
Prokaryotic translation is among the main targets of diverse natural products with antibacterial activity including several classes of clinically relevant antibiotics. In this review we summarize the information about structure, biosynthesis and mode of action of translation inhibiting RiPPs (ribosomally synthesized and post-translationally modified peptides). Azol(in)e-containing RiPPs have been known to target translation and several new compounds inhibiting the ribosome have been characterized recently. We performed a systematic search for biosynthetic gene clusters of azol(in)e-containing RiPPs. The results of the search revealed several groups of clusers that likely direct the synthesis of novel compounds, some of which may be targeting the ribosome.